2021
DOI: 10.7150/jca.45493
|View full text |Cite
|
Sign up to set email alerts
|

Demethylzelasteral inhibits proliferation and EMT via repressing Wnt/β-catenin signaling in esophageal squamous cell carcinoma

Abstract: As a kind of tumor commonly seen, no effective treatment is available for esophageal squamous cell carcinoma (ESCC). Therefore, seeking a new treatment is urgent. Demethylzeylasteral (T-96) isolated from Tripterygium wilfordii root bark embraces outstanding good antitumor activity. However, as for the mechanism of T-96 work on ESCC cells, it is rarely reported. In this study, we found that T-96 has inhibition when ESCC cells are proliferating, migrating and cloning. Moreover, relevant effects are influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Besides, Wnt signaling was reported to be inversely correlated with T cell infiltration in colorectal cancer, ( Grasso et al, 2018 ), as we also found a lower T cell infiltration in subtype 1 than in other subtypes. The Wnt signaling pathway activation is associated with tumorigenesis and progression ( Nusse and Varmus, 1992 ; Zhan et al, 2017 ; You et al, 2019 ); tumor proliferation and progression were inhibited by suppressing this pathway ( Lee et al, 2012 ; You et al, 2019 ; Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Wnt signaling was reported to be inversely correlated with T cell infiltration in colorectal cancer, ( Grasso et al, 2018 ), as we also found a lower T cell infiltration in subtype 1 than in other subtypes. The Wnt signaling pathway activation is associated with tumorigenesis and progression ( Nusse and Varmus, 1992 ; Zhan et al, 2017 ; You et al, 2019 ); tumor proliferation and progression were inhibited by suppressing this pathway ( Lee et al, 2012 ; You et al, 2019 ; Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T-96 could reduce immunocompetent cells and inflammatory mediators in the rabbit model of atherosclerosis [ 19 ], inhibit inflammatory responses in mice with lupus nephritis [ 20 – 22 ], and suppress RNA-dependent RNA polymerase of hepatitis C virus [ 23 ]. Additionally, T-96 demonstrates anti-cancer abilities by inhibiting angiogenesis, cell proliferation, and cell apoptosis [ 15 , 24 27 ]. Accumulating evidence suggests that T-96 may have the potential to be used in COVID-19 [ 28 ], arthritis [ 22 ], and other autoimmune disorders [ 22 , 28 ] as a novel therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%